PENERAPAN MODEL STAD UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA KELAS VB SDIT INSANTAMA - Marsambas, Marsambas; Mastori, Mastori (DIRASATUL IBTIDAIYAH, 2023)
This research was motivated by the finding of the VB SDIT Insantama class when a science lesson on Respiratory Organs in Ruminant Animals, that 83.87% of students had not been able to reach the KKM or 16.13% of students had reached the KKM. So it is categorized as low learning outcomes. The aim of this learning improvement is to improve science learning outcomes through the application of the STAD Model Cooperative Learning Strategy. This research took place at SDIT Insantama Bogor. The research subjects were Class VB students with a total of 31 students. Implementation was carried out in two cycles, with a pre-cycle being carried out previously. The pre-cycle was held on August 24 2021. The first cycle was carried out on September 7 2021 and the second cycle was carried out on September 14 2021. The results showed an increase, the average value in the pre-cycle was 52.58% to 69.03% in the first cycle and 85.97% in the second cycle. Based on the results, it can be concluded that the implementation of the STAD Model Cooperative Learning Strategy can improve the learning outcomes of Class VB students at SDIT Insantama Bogor for the 2021/2022 academic year. Keywords: Learning Outcomes; STAD; Science.